Lectotypification of the name Linaria tonzigii Lona (Plantaginaceae) - Orsenigo, Simone; Galasso, Gabriele (Phytotaxa, 2019)
This contribution is related to the initiative “The Italian loci classici census”, aimed at locating the original material of vascular plants described from Italy, to increase their systematic knowledge and promote further studies (Domina et al. 2012, Passalacqua et al. 2014, Peruzzi et al. 2015). During the analysis of systematic and nomenclatural aspects of the species involved, some difficulties related to the identification of original material have been pointed out. Our contribution has the aim to identify the type material of Linaria tonzigii Lona (1949: 66).